Iron Man. Vol. 3, Books of Korvac III, Cosmic Iron Man - Cantwell, Christopher (Marvel Worldwide, Inc., 2022)
"Iron Man finds himself marooned in a small colony on a remote planet! Life here seems perfect...but who's pulling the strings behind its delicate design? As Tony digs deeper for answers, a message from home warns him that Korvac is still a threat...but recovering from his many recent injuries means pain medication. Will Tony succumb to the temptation that has plagued him for years? Either way, Iron Man will soon face a cosmic showdown on the deck of Galactus' worldship. And if he manages to survive unscathed, he must battle Korvac's zealous and powerful disciples: the Controller, the Unicorn, Blizzard -- and a robotically enslaved Original Human Torch! Tony sure could use some friends right about now..."--Provided by publisher.